Thermal conductivity of bulk boron nitride nanotube sheets and their epoxy‐impregnated composites. Issue 8 (10th March 2016) - Jakubinek, Michael B.; Niven, John F.; Johnson, Michel B.; Ashrafi, Behnam; Kim, Keun Su; Simard, Benoit; White, Mary Anne
Abstract : The thermal conductivity of bulk, self‐supporting boron nitride nanotube (BNNT) sheets composed of nominally 100% BNNTs oriented randomly in‐plane was measured by a steady‐state, parallel thermal conductance method. The sheets were either collected directly during synthesis or produced by dispersion and filtration. Differences between the effective thermal conductivities of filtration‐produced BNNT buckypaper (∼1.5 W m −1  K −1 ) and lower‐density as‐synthesized sheets (∼0.75 W m −1  K −1 ), which are both porous materials, were primarily due to their density. The measured results indicate similar thermal conductivity, in the range of 7–12 W m −1  K −1, for the BNNT network in these sheets. High BNNT‐content composites (∼30 wt.% BNNTs) produced by epoxy impregnation of the porous BNNT network gave 2–3 W m −1  K −1, more than 10× the baseline epoxy. The combination of manufacturability, thermal conductivity, and electrical insulation offers exciting potential for electrically insulating, thermally conductive coatings and packaging. Thermal conductivity of free‐standing BNNT buckypaper, buckypaper composites, and related materials at room temperature.